2014
DOI: 10.7567/jjap.54.01ag04
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and plasma-catalytic oxidation of acetone over zeolite-supported silver catalyst

Abstract: The abatement of acetone using a combination of non-thermal plasma, catalysis and adsorption was investigated in a dielectric barrier discharge plasma reactor packed with silver-coated zeolite pellets serving as both adsorbent and catalyst. The removal of acetone in this reactor system was carried out by cyclic operation comprising two repetitive steps, namely, adsorption followed by plasma-catalytic oxidation. The effects of the zeolitesupported silver catalyst on the reduction of unwanted ozone emission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Details of the voltage measurement are described elsewhere [29]. The discharge power was calculated from the so-called voltage-charge Lissajous figures.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the voltage measurement are described elsewhere [29]. The discharge power was calculated from the so-called voltage-charge Lissajous figures.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Hence, the selection of an ozone decomposition catalyst with a long-term stability at low temperature should be considered, especially for the two-stage arrangement. The use of oxygen plasma is ineffective unless a cyclic treatment (i.e., VOC adsorption followed by oxygen plasma oxidation) is applied [28,29].…”
Section: Catalytic Activities Of Prepared Catalysts For Ozone Decompomentioning
confidence: 99%
“…where: C1 = 28958, C2 = 9390, C3 = 3012, C4 = 7580, and C5 = 1484 Using Equation (4), for heating the feed gas from room temperature (25 °C ) to activation temperature of the Pd/ZSM-5 (470 °C ), SIE was calculated to be 13,309,079 J/kmol, which corresponded to 544 J/L. Meanwhile, the SIE of continuous plasma and adsorption and plasma-catalytic oxidation was calculated through Equations (5) and (6) To perform a comparison between thermal catalyst oxidation, plasma-catalytic oxidation, and cyclic adsorption and plasma-catalytic oxidation, the specific input energy (SIE) for these processes was calculated. According to TPO of C 2 H 4 , the operating temperature required to activate all catalyst sites is 470 • C, suggesting heating up the feed gas from 25 • C (room temperature) to 470 • C. The SIE for heating the feed gas can be estimated through Equation (2).…”
Section: Removal Of C 2 H 4 By a Cyclic Adsorption-plasma Oxidation Pmentioning
confidence: 99%
“…Using Equation (4), for heating the feed gas from room temperature (25 • C) to activation temperature of the Pd/ZSM-5 (470 • C), SIE was calculated to be 13,309,079 J/kmol, which corresponded to 544 J/L. Meanwhile, the SIE of continuous plasma and adsorption and plasma-catalytic oxidation was calculated through Equations (5) and (6) To sum up, the SIE for the thermal oxidation, continuous plasma oxidation, and the adsorption and plasma-catalytic oxidation are plotted in Figure 7. This figure indicates that the continuous plasma not only oxidizes the C 2 H 4 at low temperature but also decreases the requirement of input energy (450 J/L) in comparison with the thermal oxidation process.…”
Section: Removal Of C 2 H 4 By a Cyclic Adsorption-plasma Oxidation Pmentioning
confidence: 99%
“…As shown in Fig.3b the particle size of metallic silver granules on the surface of Ag/HY was about 20nm. Moreover, in the plasma combined catalysis system, the effect of ozone, adsorption/desorption and the direct interaction of gas phase radicals with catalyst surface was also related to toluene removal 10,11,29 . Moreover, Baek suggested that the metals which possessed empty s-orbits and available electrons in the d-orbits could form strong π-complexation bonding 23 , and the πcomplexation adsorption with toluene on Ag also contributed to the enhancement of adsorption abilities of Ag/HY catalyst.…”
Section: Toluene Adsorption On Various Types Of Zeolitesmentioning
confidence: 99%